Изменчивость сеянцев Aster dumosus L. ‘Blue Bouquet’ под влиянием диметилсульфата - Орлова, Т.Г. (Промышленная ботаника, 2003)
The results of the studies of morphologic peculiarities in seedlings of Aster dumosus L. ‘Blue Bouquet’ obtained under the effect of dimethylsulphate. It indicated the authentic decrease in height of the plants under the influence of mutagen. 98 undersized compact forms of Aster dumosus having good prospects for further selection, were determined.